The Role of Expert Accountants in Ensuring Regulatory Compliance with Corporate Sustainability Reporting in the European Union - Liviu Marian MATAC; Florentina PANTAZI; Paul-Tiberius COMAN; Maria BOLBOCEANU (CECCAR Business Review)

(untitled)
The Corporate Sustainability Reporting Directive (CSRD) requires companies to integrate sustainability reporting with financial data, emphasizing the role of accountants. Accountants must ensure accurate and comprehensive financial statements, reflecting both financial and non-financial impacts. They need to stay updated with legislative changes and collaborate across departments to aggregate relevant data. Accountants will identify the financial impact of sustainability factors and prepare ESG metrics, critical for securing European funding. They will also help companies assess climate risks and ensure compliance with sustainability standards, positioning sustainability at the core of decision-making processes.